2020
DOI: 10.1002/mds.28320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Subthalamic Deep Brain Stimulation on Impulse Control Disorders in Parkinson's Disease: A Prospective Study

Abstract: Background Impact of subthalamic deep brain stimulation (DBS) on impulse control disorders (ICD) in Parkinson's disease (PD) remains controversial. Objectives The objectives of this study were to analyze the natural history of ICD between baseline and 1 year after subthalamic DBS in patients with PD and to identify predictive factors, taking into account the positions of the active contact and stimulation parameters. Methods We analyzed postoperative modifications of ICD based on the multicentric, prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
3
28
0
3
Order By: Relevance
“…In the absence of a blinded RCT, the effect of chronic STN-DBS on ICD and DDS is estimated from several prospective studies and summaries of the available retrospective and prospective patient series. 6,76 Early case reports described improvements in dopamine addiction 77 and pathological gambling 78 in parallel to the postoperative decrease in dopaminergic medication. Since then, larger cohorts from several independent centers followed for periods of up to 7 years supported the overall beneficial long-term effect of STN-DBS on ICD.…”
Section: Impulse Control and Related Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of a blinded RCT, the effect of chronic STN-DBS on ICD and DDS is estimated from several prospective studies and summaries of the available retrospective and prospective patient series. 6,76 Early case reports described improvements in dopamine addiction 77 and pathological gambling 78 in parallel to the postoperative decrease in dopaminergic medication. Since then, larger cohorts from several independent centers followed for periods of up to 7 years supported the overall beneficial long-term effect of STN-DBS on ICD.…”
Section: Impulse Control and Related Disordersmentioning
confidence: 99%
“…Dopamine agonist dose reduction was the main driver of ICD improvement. 6,79 Desensitization consecutive to a decrease in dopaminergic medications, together with a decrease in ondrug euphoria, seemed to represent the basic mechanism. 15 Systematic improvement of ICD has not been reported in GPi-DBS, 80 which likely reflects the fact that GPi-DBS generally does not allow for a substantial decrease in dopaminergic medication.…”
Section: Impulse Control and Related Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether nonpharmacological interventions such as deep brain stimulation (DBS) ameliorates or worsens ICRBs in PD patients is still debated. While most human studies indicated that DBS improves PD + ICD, some have reported the development of shortterm de novo ICDs following DBS (Amami et al, 2015;Rossi et al, 2017;Kim et al, 2018;Lo Buono et al, 2020;Santin et al, 2020). In rodents, decreased risk-taking and losschasing was reported following lesioning to the subthalamic nucleus (STN), possibly pinpointing this region as a target for DBS and other treatments for PD + ICD (Breysse et al, 2020).…”
Section: Treatments For Pd + Icdmentioning
confidence: 99%
“…Nicht alle ausgeprägten Psychopathologien stellen Kontraindikationen für die THS dar. Medikamentös induzierte psychische Symptome wie Impulskontrollstörungen oder Halluzinationen können -den Ausschluss einer Demenz vorausgesetzt -sogar eine Indikation für die THS darstellen, da diese Symptome im Zusammenhang mit der nach der THS möglichen Dosisreduktion der dopaminergen Medikation verschwinden oder sich dramatisch bessern können [18]. Neben einer Demenz kann eine schwere Depression eine Kontraindikation für die THS darstellen, insbesondere auch unter dem Gesichtspunkt einer (allerdings kontrovers diskutierten) erhöhten Suizidrate in den ersten Jahren nach THS, wobei prä operativ eine bestehende Depression einen Risikofaktor darstellt [19].…”
Section: Geschichte Und Entwicklung Der Thsunclassified